Pengaruh Kepuasan Pelanggan, Harga, dan Promosi Terhadap Loyalitas Pelanggan Yoga Nature Class Podomoro Park - Aprilia Nurfadhilah; Nugraha Saefudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of customer satisfaction, price, and promotion on customer loyalty in the Sunday yoga class at Yoga Nature Class, Podomoro Park. The research employs a quantitative approach using a survey method. The sample consists of 94 respondents who are regular participants in the Sunday yoga class held at 07.00 AM. The research instrument is a questionnaire using a Likert scale. Data were analyzed through validity and reliability tests, descriptive analysis, classical assumption tests, and multiple linear regression analysis. The results show that, partially, customer satisfaction, price, and promotion each have a positive and significant effect on customer loyalty. Simultaneously, the three variables also significantly influence customer loyalty. These findings indicate that improvements in satisfaction, appropriate pricing, and effective promotional strategies can enhance participants’ loyalty to the weekly yoga class. In conclusion, customer satisfaction, price, and promotion are key factors in building customer loyalty in fitness service offerings such as yoga classes. This study is expected to provide valuable insights for the management of Yoga Nature Class in designing more customer-oriented marketing strategies.